Dynamic forces and processes in the rails under impact interaction of wheels with defects - O. G. Krasnov; O. K. Bogdanov; M. G. Akashev (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
The paper presents the main results of comprehensive experimental studies on the determination of regularities of dynamic processes and actual values of the forces of interaction of wheels with defects on rolling surface and rails on the modern designs of the track, carried out at the experimental section of railway track. It was determined experimentally that: dynamic processes of interaction of wheels with defects such as flats, weld-on, uneven rolling have specific shape and phase marked by the geometrical shape of defects; dependencies on impact forces to the flat-type defects were approximated by a polynomial function with the highest levels of forces in the speed range of 50 - 70 km/h. For defects such as weld-on or uneven rolling marked by impact forces with increasing speed; all the above types of defects are marked by considerable variation of levels of impact forces for the same modes of running (speed, direction), which is connected with meandering nature of the movement of wheelset, determining differences in the interaction of wheel and rail; dynamic impact loads initiate pulsed total deflection of rail in the vertical direction and the horizontal transverse motion. Values of total vertical deflection reach 8 - 9 mm for the values of impact forces of 400 - 450 kN that is 3.5 - 4 times more than the quasi-static motion of rolling stock; dynamic impact impulse excites damped oscillatory processes in vertical and horizontal directions with decay time 0.1 - 0.12 seconds. The levels of vertical acceleration in the rails with impact forces of 400 - 450 kN reached 191 - 258 m/s. The spectrums of vertical oscillations dominated oscillations with a frequency of 6.4, 50 - 60, 90 - 110 Hz. The presence of high-frequency components is connected to the excitation of vertical vibrations of the rail-sleeper network. In the process of impact interaction rail oscillations with frequencies of 25, 75 - 80 Hz also developed laterally.